Mortality of patients with metastatic colorectal cancer who received elective or emergent operation after exposure to bevacizumab: A nationwide database study. Issue 2 (February 2023) - Chen, Yu-Hsun; Su, Yi-Chia; Hsu, Chao-Wen; Hsieh, Meng-Che; Wang, Yung-Chang; Lee, Ming-Hung; Lin, Chien-Yuan; Chang, Yu-Ching; Wu, Chih-Chien
Abstract: Introduction: Treatment guidelines for colorectal cancer (CRC) indicate that surgical intervention within 4 weeks or 8 weeks after bevacizumab therapy might increase the risk of postoperative complications and mortality, especially in patients who received emergent operation. Therefore, we aimed to assess the association between different surgical timings, emergent or elective surgery, and the risk of postoperative mortality. Materials and methods: Using the Taiwan National Health Insurance Database and Taiwan Cancer Registry, we identified patients with metastatic colorectal cancer (mCRC) who underwent surgery within 1 year of receiving bevacizumab between January 2010 and December 2017. The primary outcomes were 30-day, 60-day, and in-hospital mortality; the secondary outcomes were hospital stay, 30-day readmission rate, and surgical complications. Multivariate analysis was used to adjust for confounders. Results: This study included 2, 047 patients. In the multivariate analysis, patients who underwent emergent operation and had higher Charlson scores had a significantly higher mortality rate. Patients with a longer interval to surgery, more cycles of bevacizumab treatment, and distal metastectomy had the opposite result. In subgroup analysis, patients who received emergent operation within 28 days had the highest surgical mortality. Conclusions: The interval to operation among mCRC patients who receive bevacizumab treatment should exceed 4 weeks to avoid additional risk of mortality whether patients receiving elective or emergent operation. Patients who received emergent operation within 28 days of bevcizumab infusion had the highest risk of mortality.